Performance comparison of granular media filter beds - SOYER, ELİF (TAYLOR & FRANCIS INC, 2016)
Particle capture, head loss development, and efficiency of in-line coagulation in contact filtration were studied using two types of laboratory filters with varying coagulants. One filter consisted of sand and anthracite, whereas the other filter contained crushed glass and anthracite. Effects of in-line coagulation on filter performance were evaluated using a charge measuring device. Performance of filters was monitored in terms of effluent quality as a function of time and development of head loss by anthracite layer and by the entire filter bed. Filterability index was used to provide a measure of effectiveness of filter media and/or operational variables such as coagulant type and dosage. This study found that the crushed glass-anthracite filter was as effective at removal of particles and metals (Fe and Al) as sand-anthracite filters.
Keywords: Filter material; Filter performance; Filterability index; Metal capture; Particle counts; Turbidity; Head loss buildup; CRUSHED RECYCLED GLASS; WASTE-WATER TREATMENT; DRINKING-WATER; SILICA SAND